The Effects of CrV Underlayer on the Structure and Magnetic Properties of FePt Thin Film - Chun, DongWon; Kim, SungMan; Kim, GyeungHo; Jeung, WonYoung (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2010)
An attempt is made in this study to employ vanadium containing chromium (CrV) alloy underlayer to control the microstructure and ultimately to facilitate the in-situ ordering of Fe-Pt thin film. CrV alloys with V contents ranging from 0 to 15 at% were investigated to evaluate their effects on the magnetic properties and structural modification of FePt thin film. Addition of V in Cr underlayer results in the formation of FePt L1(0) phase with (001) preferred orientation. Analysis of XRD and HR-TEM results reveals that the lattice expansion of Cr underlayer induced by V addition increases the lattice misfit strain between CrV underlayer and FePt magnetic layer. Consequently well aligned FePt (001) grains and in-situ ordering of FePt L1(0) thin film can be obtained. Magnetic property measurements show that FePt/Pt/5.8 at.% V-Cr multilayer has the maximum out-of-plane coercivity (4000 Oe) and squareness (0.95). Due to in-situ ordering, good perpendicular magnetic properties with higher coercivity and squareness were achieved from FePt/Pt/Cr94.2V5.8 multi-layers at the processing temperature of 350 degrees C without further annealing treatment.
Keywords: LAYER